More or less aggressive? Robust monetary policy in a New Keynesian model with financial distress - Rafael Gerke; Felix Hammermann; Vivien Lewis (Verein für Socialpolitik, 2010)
This paper investigates the optimal monetary policy response to a shock to collateral when policymakers act under discretion and face model uncertainty. The analysis is based on a New Keynesian model where banks supply loans to transaction constrained consumers. Our results confirm the literature on model uncertainty with respect to a cost-push shock. Insuring against model misspecification leads to a more aggressive policy response. The same is true for a shock to collateral. A preference for robustness leads to a more aggressive policy. Increasing the weight attached to interest rate smoothing raises the degree of aggressiveness. Our results indicate that a preference for robustness crucially depends on the way different types of disturbances affect the economy: in the case of a shock to collateral the policymaker does not need to be as much worried about model misspecification as in the case of a conventional cost-push shock.
Keywords: E58; E44; E32; 330; optimal monetary policy discretion; model uncertainty; banking; collateral